2011
DOI: 10.5465/amj.2010.0179
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Effects of Sleep Deprivation on Workplace Deviance: A Self-Regulatory Perspective

Abstract: The causes of workplace deviance are of increasing interest to organizations. We integrate psychological and neurocognitive perspectives to examine the effects of sleep deprivation on workplace deviance. Utilizing self-regulatory resource theories, we argue that sleep deprivation decreases individuals' self-control while increasing hostility, resulting in increased workplace deviance. We test our hypotheses using two samples: one comprised of nurses from a large medical center and another comprised of undergra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
445
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 447 publications
(485 citation statements)
references
References 115 publications
14
445
4
Order By: Relevance
“…State hostility fully mediates the relationship between sleep deprivation and workplace deviance therefore Hypothesis 3 is also rejected. These results are different from that of Christian and Ellis [68], in which they have used Baron and Kenny approach to mediation, and Preacher and Hayes approach to bootstrapping multimediators. The hypothesis in their study has been accepted in which both self-control and hostility partially mediates the relationship between sleep deprivation and workplace deviance.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…State hostility fully mediates the relationship between sleep deprivation and workplace deviance therefore Hypothesis 3 is also rejected. These results are different from that of Christian and Ellis [68], in which they have used Baron and Kenny approach to mediation, and Preacher and Hayes approach to bootstrapping multimediators. The hypothesis in their study has been accepted in which both self-control and hostility partially mediates the relationship between sleep deprivation and workplace deviance.…”
Section: Discussioncontrasting
confidence: 45%
“…6 hours was chosen as the cut-off point because sleeping less than 6 hours will damage the cognitive capacity, while sleeping 7 or more will not [55], [68]. Bonnet and Arand (1995) and Weinger and Ancoli Israel [52] found that 5 to 6 hours of sleep has a detrimental effect on mood, performance, and alertness.…”
Section: Sleep Deprivationmentioning
confidence: 99%
See 2 more Smart Citations
“…Managing employee stress is increasingly important due to trends such as long work hours, tight deadlines, and increased pressure to achieve organizational goals (e.g., Perlow, 1998Perlow, , 2012. Such work settings may easily lead employees to feel depleted, and promote workplace deviance associated with self-regulation failure (e.g., Christian & Ellis, 2011). The effect of reminders of new money on reducing workplace deviance or promoting organizational citizenship behavior is worth exploring.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%